Optimal Precoder Selection for Spatially Multiplexed Multiple-Input Multiple-Output Systems With Maximum Likelihood Detection: Exploiting the Concept of Sphere Decoding - Woosung Hwang; Jaeyoung Park; Jaekwon Kim; Hyo-Sang Lim (IEEE Access, 2020)
In this paper, a computationally efficient implementation technique for optimal precoder selection in spatially multiplexed (SM) multiple-input multiple-output (MIMO) systems with maximum-likelihood detection at the receiver is proposed. The techniques previously developed for suboptimal precoder selection were based on the lower bounds of the free distances of precoders to reduce the processing time. However, the use of these techniques leads to significant declines in error performance when the number of spatial streams approaches the number of receiving antennas. At the same time, to achieve optimal performance, the conventional optimal precoder selection technique can be employed; however, it has a long processing time due to exhaustive search. Thus, in this paper, we propose a precoder selection technique that maintains an optimal performance without the prohibitive processing time of the conventional optimal precoder selection. The processing time can be reduced by the following: (1) exploiting the symmetric structure of quadrature amplitude modulation (QAM) constellations, thereby reducing the search space; (2) adopting the concept of sphere decoding (SD); (3) eliminating the last stage of SD; and (4) performing an SD-like process in a selective manner. Both the optimal performance and reduction in the processing time realized by the proposed technique are confirmed via simulation.